(3GdQJHI aj WQGFb GdMSHIs - (3YHO GdQMef Hf fUQ GdSfGejs
(3ChdgG (B:s
(3bGd GdTjN GdUGdM YHO GdQMef GdHGH GdChd ajeG jLH Ydi GdeMJSH ef TQhW GdMSHI hQShe eSJMHGJgG s
(3BNQgG (B:s
(3hdgPG PcQfG ai Chd GdcJGH Cfg jLH Cf jchf GdeMJSH YGdekG aEfg Ef cGf LGgdkG EMJGWJ Ydjg GdCehQ hbY ai GdeMXhQ Je gPG GdcJGH GdZQj HMeO Gddg hYhfg hMSf Jhajbg hdgh NjQ eYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs